Colchicine and aspirin in community patients with COVID-19 (ACT): an open-label, factorial, randomised, controlled trial. Issue 12 (December 2022) - Eikelboom, John W; Jolly, Sanjit S; Belley-Cote, Emilie P; Whitlock, Richard P; Rangarajan, Sumathy; Xu, Lizhen; Heenan, Laura; Bangdiwala, Shrikant I; Tarhuni, Wadea M; Hassany, Mohamed; Kontsevaya, Anna; Harper, William; et al.
Summary: Background: The large number of patients worldwide infected with the SARS-CoV-2 virus has overwhelmed health-care systems globally. The Anti-Coronavirus Therapies (ACT) outpatient trial aimed to evaluate anti-inflammatory therapy with colchicine and antithrombotic therapy with aspirin for prevention of disease progression in community patients with COVID-19. Methods: The ACT outpatient, open-label, 2 × 2 factorial, randomised, controlled trial, was done at 48 clinical sites in 11 countries. Patients in the community aged 30 years and older with symptomatic, laboratory confirmed COVID-19 who were within 7 days of diagnosis and at high risk of disease progression were randomly assigned (1:1) to receive colchicine 0·6 mg twice daily for 3 days and then 0·6 mg once daily for 25 days versus usual care, and in a second (1:1) randomisation to receive aspirin 100 mg once daily for 28 days versus usual care. Investigators and patients were not masked to treatment allocation. The primary outcome was assessed at 45 days in the intention-to-treat population; for the colchicine randomisation it was hospitalisation or death, and for the aspirin randomisation it was major thrombosis, hospitalisation, or death. The ACT outpatient trial is registered at ClinicalTrials.gov, NCT04324463 and is ongoing. Findings: Between Aug 27, 2020, and Feb 10, 2022, 3917 patients were randomly assigned to colchicine or control and to aspirin or control; after excluding 36 patients due to administrative reasons 3881 individuals were included in the analysis (n=1939 colchicine vs n=1942 control; n=1945 aspirin vs 1936 control). Follow-up was more than 99% complete. Overall event rates were 5 (0·1%) of 3881 for major thrombosis, 123 (3·2%) of 3881 for hospitalisation, and 23 (0·6%) of 3881 for death; 66 (3·4%) of 1939 patients allocated to colchicine and 65 (3·3%) of 1942 patients allocated to control experienced hospitalisation or death (hazard ratio [HR] 1·02, 95% CI 0·72–1·43, p=0·93); and 59 (3·0%) of 1945 of patients allocated to aspirin and 73 (3·8%) of 1936 patients allocated to control experienced major thrombosis, hospitalisation, or death (HR 0·80, 95% CI 0·57–1·13, p=0·21). Results for the primary outcome were consistent in all prespecified subgroups, including according to baseline vaccination status, timing of randomisation in relation to onset of symptoms (post-hoc analysis), and timing of enrolment according to the phase of the pandemic (post-hoc analysis). There were more serious adverse events with colchicine than with control (34 patients [1·8%] of 1939 vs 27 [1·4%] of 1942) but none in either group that led to discontinuation of study interventions. There was no increase in serious adverse events with aspirin versus control (31 [1·6%] vs 31 [1·6%]) and none that led to discontinuation of study interventions. Interpretation: The results provide no support for the use of colchicine or aspirin to prevent disease progression or death in outpatients with COVID-19. Funding: Canadian Institutes for Health Research, Bayer, Population Health Research Institute, Hamilton Health Sciences Research Institute, and Thistledown Foundation. Translations: For the Portuguese, Russian and Spanish translations of the abstract see Supplementary Materials section.